Pelatihan Penelusuran Informasi Online Melalui Media Sosial (Pelatihan kepada Siswa/i SMPN 88 Jakarta Barat) - Vinta Sevilla; Ratu Nadya Wahyuningratna (Universitas Persada Indonesia YAI, 2023)
Information is one of the basic human needs in everyday life. At first information is an expensive thing andrequires effort to get it, such as having to buy newspapers, books, magazines, and so on. But along with thedevelopment of technology, now information is no longer something that is difficult to obtain. Information can beaccessed anywhere and anytime, and is not limited by space and time. One of the media that is widely used by thepublic to find information today is social media. The use of social media by the Indonesian people was 191 millionpeople in January 2022. This number has increased by around 12.35% compared to the previous year, which was 170million people. In the implementation of this community service activity, the author provides training to students atSMPN 88 West Jakarta. This activity is given to Junior High School (SMP) students because they are active users ofsocial media in searching for information. The variety of information in the digital space, it is necessary to providetraining to junior high school students so that they are not mistaken in using, searching and searching for information.Based on the evaluation results and findings in this activity, it can be concluded that the students of SMPN 88 WestJakarta have used social media relatively well and still need assistance to find references that have credibility.